Distribution Pattern and Mapping of Invasive Alien Species Bellucia pentamera in Conservation Area of PT. Tidar Kerinci Agung (TKA) Solok Selatan - Uswatul Inayah; Solfiyeni Solfiyeni (Jurnal Biologi Universitas Andalas, 2021)
Bellucia pentamera is one of the most dangerous invasive alien species for environment. This species had been invaded many forests in Indonesia. This species would invade more area due to deforestation. The objectives of this study were to know the mapping and distribution pattern of B. pentamera; to know the effects of distance from road and light intensity to distribution of B. pentamera. This study was conducted from March to August 2020 in Conservation Area of PT. TKA Solok Selatan using belt transect method by plotting 20x50 m2. Data was analyzed using Morishita Index and Linear Regression. Distribution pattern of B. pentamera in PT. TKA was clumped, showed by 1.17 of Morishita index. Seedlings and saplings of B. pentamera were dominant at the edge of conservation forest while trees were distributed from the middle to inside of the forest. Distance from road gave positively effects and significantly towards distribution of B. pentamera showing result 0.702 of R2 and 0.007 of p-Value. Light intensity did not give effects significantly towards distribution of B. pentamera showing result 0.0806 of R2 and 0.427 of p-Value.